New mesh-type phantoms and their dosimetric applications, including emergencies. (October 2018) - Kim, C.H.; Yeom, Y.S.; Nguyen, T.T.; Han, M.C.; Choi, C.; Lee, H.; Han, H.; Shin, B.; Lee, J-K.; Kim, H.S.; Zankl, M.; Petoussi-Henss, N.; et al.
Committee 2 of the International Commission on Radiological Protection (ICRP) has constructed mesh-type adult reference computational phantoms by converting the voxel-type ICRP Publication 110 adult reference computational phantoms to a high-quality mesh format, and adding those tissues that were below the image resolution of the voxel phantoms and therefore not included in the Publication 110 phantoms. The new mesh phantoms include all the necessary source and target tissues for effective dose calculations, including the 8–40-µm-thick target layers of the alimentary and respiratory tract organs, thereby obviating the need for supplemental organ-specific stylised models (e.g. respiratory airways, alimentary tract organ walls and stem cell layers, lens of the eye, and skin basal layer). To see the impact of the new mesh-type reference phantoms, dose coefficients for some selected external and internal exposures were calculated and compared with the current reference values in ICRP Publications 116 and 133, which were calculated by employing the Publication 110 phantoms and the supplemental stylised models. The new mesh phantoms were also used to calculate dose coefficients for industrial radiography sources near the body, which can be used to estimate the organ doses of the worker who is accidentally exposed by an industrial radiography source; in these calculations, the mesh phantoms were deformed to reflect the size of the worker, and also to evaluate the effect of posture on dose coefficients.